Load Balanced Network: Design, Implementation and Legal Consideration Issues - Abuonji, Paul; Rodrigues, Anthony J.; Raburu, George O. (Discoveries in Agriculture and Food Sciences, 2018)
Computer networks have become extremely useful in the modern fast paced work and business environments. Every user of a computing device- desktops, laptops, tablets and mobile phones- wants to connect to a network and communicate with others in near real-time. So networks have become largely ubiquitous. However many challenges exist for perfect network ubiquity. To many users, a network is not useful if they cannot access it when they need it. Many factors such as congestion, disconnection, misconfiguration, network loops, host-source outage and device errors lead to unavailability of a network or network enabled services. This study focused on the design, implementation and legal issues of load balanced networks in order to increase the availability of bandwidth supply. Several network designs were developed and tested situ in a real organization and resulting data used to make decisions on what adjustments to make in the subsequent designs until the best design was achieved in an iterative manner.